Mothers’ Knowledge Regarding Prevention of Home Accidents Among Toddlers: A Cross-Sectional Study - Narendra Pal Singh Choudhary; A Doris Lily; Soni Chauhan; Surya Kant Tiwari (RGUHS Journal of Nursing Sciences)
Background and aim Home accidents are a leading cause of mortality and morbidity among young children. Effective prevention of home accidents relies on a combination of protection and education with mothers playing a significant role as primary caregivers. This study aimed to assess mothersrsquo knowledge regarding the prevention of home accidents among toddlers.Methods A descriptive cross-sectional study was conducted from July 2023 to September 2023 among mothers of toddlers aged 1-3 years in Jaipur using a convenient sampling technique. Data were collected using a structured multiple-choice questionnaire with 30 items across eight domains related to home accident prevention.ResultsA descriptive survey included 100 mothers predominantly aged 21-25 years Hindus and with primary education. Most mothers had moderate knowledge 61 about preventing home accidents whereas 14 had inadequate knowledge. The highest knowledge was in the domains of foreign body aspiration 80.25 and general information about home accidents 74.83 while the lowest was in drowning 48.66. Significant associations were found between mothers knowledge and demographic variables such as age education occupation family income type of family number of toddlers type of house and source of knowledge.Conclusion This study highlights that while most mothers possess moderate knowledge regarding the prevention of home accidents among toddlers critical gaps remain particularly in drowning prevention. Enhancing educational efforts and integrating safety education into routine healthcare and community programs are essential to reduce the incidence of preventable home accidents among toddlers thereby safeguarding their health and wellbeing.